Developing Long Term Low Emissions and Climate Resilient Agricultural Development Pathways for Zambia: Capacity needs and strengthening technical and institutional capacities - African Group of Negotiators Expert Support; Food and Agriculture Organization of the United Nations; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Development of Agriculture LTS is a highly technical, multi-step process that underpins formulation of specific long-term trajectory based on projected future climate scenarios. It requires countries to address data needs, uncertainties and the choice of adequate models as well as existing capacities to use them. In formulating Agriculture LTS for Zambia, the process included framing and contextualizing future emissions and future climate scenarios. This provided the basis for generating and prioritizing climate actions for achieving more sustainable and impactful solutions in the country.